Evolution of shore hardness under uniaxial tension/compression in body-temperature programmable elastic shape memory hybrids - Naveen, Balasundaram Selvan (2023)
Body-temperature programmable elastic shape memory hybrids (SMHs) have great potential for the comfortable fitting of wearable devices. Traditionally, shore hardness is commonly used in the characterization of elastic materials. In this paper, the evolution of shore hardness in body-temperature programmable elastic SMHs upon cyclic loading, and during the shape memory cycle, is systematically investigated. Upon cyclic loading, similar to the Mullins effect, significant softening appears, when the applied strain is over a certain value. On the other hand, after programming, in general, the measured hardness increases with increase in programming strain. However, for certain surfaces, the hardness decreases slightly and then increases rapidly. The underlying mechanism for this phenomenon is explained by the formation of micro-gaps between the inclusion and the matrix after programming. After heating, to melt the inclusions, all samples (both cyclically loaded and programmed) largely recover their original hardness.